2021
DOI: 10.26565/2312-4334-2021-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Novel Phosphonium Dye with Lipid Bilayers: A Fluorescence Study

Abstract: The phosphonium-based optical probes attract ever growing interest due to their excellent chemical and photophysical stability, high aqueous solubility, long wavelength absorption and emission, large extinction coefficient, high fluorescence quantum yield, low cytotoxicity, etc. The present study was focused on assessing the ability of the novel phosphonium dye TDV to monitor the changes in physicochemical properties of the model lipid membranes. To this end, the fluorescence spectral properties of TDV have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Specifically, it was demonstrated that TDV can be effectively used for optical detection of disease-related protein aggregates [54,55] and for elucidating the mechanisms of DNA interactions with amyloid fibrils [56]. Moreover, it was shown previously that TDV is highly suitable for membrane studies since it possesses a pronounced lipid-associating ability and high sensitivity to physicochemical properties of the model lipid bilayers [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was demonstrated that TDV can be effectively used for optical detection of disease-related protein aggregates [54,55] and for elucidating the mechanisms of DNA interactions with amyloid fibrils [56]. Moreover, it was shown previously that TDV is highly suitable for membrane studies since it possesses a pronounced lipid-associating ability and high sensitivity to physicochemical properties of the model lipid bilayers [57].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study the molecular dynamics simulation was used to explore the interaction between TDV and the model lipid membranes with the main emphasis on determining the depth of the probe location in a lipid bilayer. Besides, it was assumed previously that membrane electrostatics plays an important role in the membrane association of TDV [57]. Therefore, it was also interesting to assess the role of TDV charge in the dye membrane partitioning.…”
Section: Resultsmentioning
confidence: 99%